(untitled) (Research, Society and Development, 2022)
Introduction: Paraccocideoides brasiliensis (Pb) is a fungal pathology that causes serious lesions in the mouth in the form of ulcerations that destroy the gingiva, palate, reflecting on the immune system. For the treatment of Paracoccidioidomycosis (PMC) the choice of drug is based on the degree of the disease, with Amphotericin B (AB) being the most used due to its mechanism of action and interaction with the fungal membrane, causing its destruction. However, with all the history of AB toxicity, there is a need to reduce the serum levels of the drug in the body. The use of nanoparticles as controlled release systems (DDS) is an alternative for this purpose. The objective of this article was to develop gelatin nanoparticles for the treatment of pathologies caused by Pb. Method: In this work, gelatin nanoparticles were processed by the two-step desolvation method and loaded with AB. The nanoparticulate system was characterized by scanning electron microscopy (SEM) and dynamic light scattering (DLS). Finally, the effectiveness of DDS was evaluated against Pb yeasts by Disk Diffusion Test. Results: the synthesized particles presented suitable sizes and shapes for application in DDS with an average size of 169.4 and 172.0 nm, for the free and encapsulated system, respectively. Biological model tests of Pb showed positive results indicating that lower concentrations of AB can be efficiently administered if nanostructured DDS is used. Conclusion: This study is promising for future applications of AB-loaded gelatin nanoparticles for the treatment of pathologies caused by Paraccocideoides brasiliensis.